Perceptions and worries about monkeypox, and attitudes towards monkeypox vaccination among medical workers in China: A cross-sectional survey. Issue 3 (March 2023) - Peng, Xin; Wang, Bingyi; Li, Yuwei; Chen, Yuanyi; Wu, Xinsheng; Fu, Leiwen; Sun, Yinghui; Liu, Qi; Lin, Yi-Fan; Liang, Bingyu; Fan, Yinguang; Zou, Huachun
Abstract: Background: The World Health Organization (WHO) declared monkeypox a "public health emergency of international concern" on 23 June 2022. However, there is a lack of data on monkeypox perceptions among medical workers. The purposes of this study were to evaluate perceptions, worries about monkeypox, attitudes towards monkeypox vaccination and their correlates among medical workers in China. Methods: Data were collected from medical practitioners using an online survey questionnaire between September 1 and September 30, 2022 in China. All the subjects completed an online questionnaire including general characteristics, perceptions/knowledge/worries about monkeypox, and attitudes towards monkeypox vaccination. Logistic regression was employed to examine the correlates of perceptions, worries about monkeypox, and attitudes toward monkeypox vaccination. Results: In total, this study sample included 639 medical workers. The mean age was 37.9 ± 9.4 years old. Approximately 71.8% of individuals reported perceptions of monkeypox, 56.7% worried about monkeypox, and 64.9% supported the promotion of monkeypox vaccination. Medical workers who were older than 50 years (aOR 3.73, 95%CI 1.01–13.85), worked in the Infectious Diseases/Dermatology/Venereal Diseases departments (3.09, 1.61–5.91), and provided correct answer to monkeypox transmission route (10.19, 5.42–19.17) were more likely to know about monkeypox/monkeypox virus before investigation. 30.7% reported that they were more worried about monkeypox than the coronavirus (COVID-19). Participants reported that the key population most in need of monkeypox vaccination were health practitioners (78.2%) and people with immunodeficiency (74.3%), followed by children (65.4%) and older adults (63.2%). Conclusion: Awareness of monkeypox was high and attitude towards the promotion of monkeypox vaccination was positive among medical staff in China. Further targeted dissemination of monkeypox common knowledge among health care providers might improve their precaution measures and improve the promotion of monkeypox vaccination among key populations.